Academic Dishonesty Identification through Gender and Grade Using Chi-Square Analysis - Dewi Kurniawati; Tika Dwi Ariyanti (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Academic dishonesty, as a cheating act done by students, has always been a significant challenge in education. It reflects integrity and responsibility as the main element in character development. Many studies had done to identify variables behind students' dishonesty. Hensley (2013) said male students are likelier to cheat and plagiarise. This study measured further through a perspective questionnaire using a vignette test for vocational education during an online class. The variables were designed based on Maslow's hierarchy of needs with six dependent and five independent variables. The analysis of this study applied chi-square quantitative analysis. At the same time, the data was collected using random sampling from semesters 1,3 and 5 of the Informatics Engineering study program in Politeknik Negeri Jakarta. This study was conducted during COVID -19 Pandemic when all the teaching, learning and assessment processes were conducted online. This study showed that gender and grade did not affect students’ motivation to cheat during online exams. At the same time, the chi-square analysis reflected the same result for both gender and grade analysis. They did not highly influence academic dishonesty in the online test. This study exposed us to varied insights into variables behind academic dishonesty, such as religiosity, lecturer and course and system. This finding triggered further study and evaluation of the institution system and human resource development since they had a role in shifting the phenomena.